Emotion-Focused Coping with the Increasing Cost of Living: Insights from Middle-Income Households in Klang Valley - Kasim, Nor Hasniah; Abu Bakar Ah, Siti Hajar; Zakaria, Roza Hazli (The Malaysian Journal of Social Administration, 2025)
The increasing cost of living significantly affects urban middle-income households in Klang Valley, Malaysia, prompting various coping strategies to manage associated stress. This qualitative study examines emotion-focused coping strategies through in-depth interviews with eight middle-income participants. Thematic analysis identified four primary strategies: seeking social support, mental disengagement, acceptance, and religious coping. Participants sought emotional support from close relationships, found temporary relief through activities like hiking or cooking, and embraced acceptance to confront challenges and foster resilience. Religious coping, including prayer and acts of charity, provided solace and emotional strength. While these strategies alleviate emotional distress and promote resilience, they do not address the root economic challenges. The findings emphasise the importance of integrating emotion-focused and problem-focused approaches to support households facing financial stress.